PROTECTIVE EFFECTS OF VICIA HIRSUTA AGAINST HYPOXIA- INDUCED LETHALITY IN MICE: Pharmaceutical Science-Pharmacology - MARAL YAZDANPANAH; ZAHRA MOUSAVI; MOHAMMAD ALI EBRAHIMZADEH (International Journal of Life Science and Pharma Research, 2022)
Vicia (Papilionaceae) has 45 species in Iran. Many biological activities have been reported from this genus. Several medicinal plants have accepted antihypoxic activities. Nothing is known about protective effects of Vicia hirsuta against hypoxia-induced lethality. In this study, the protective effects of V. hirsute aerial parts against hypoxia-induced lethality in mice were evaluated by three experimental models of hypoxia, asphyctic, haemic and circulatory. Statistically significant protective activities were established in some model of hypoxia in mice. Antihypoxic activity was especially pronounced in asphytic and haemic hypoxia. These effects were dose-dependent. Extracts at all tested doses, showed statistically significant activities respect to the control.In asphytic hypoxia, at 100 mg kg-1, extract significantly prolonged the latency for death with respect to control group (51.00 ± 6.05 vs. 33.67 ± 4.50 min, p<0.001). Phenytoin kept mice alive for 55.00 ± 6.05 min. In haemic model, control group died of hypoxia in 7.87 ± 0.78 min. Extract at 100 mg kg-1 significantly prolonged latency for death with respect to control group (15.60 ± 1.34 min, p<0.001). In circulatory hypoxia, extract at 100 mg kg-1, significantly prolonged the latency for death with respect to control group (14.83 ± 0.75 vs. 10.71 ± 1.12 min, p<0.001). Vicia hirsuta showed a very good protective effect against the hypoxia in some model. The presence of polyphenols in this plant may be a proposal mechanism for reported antihypoxic activities of this plant.